Therapeutic effects of creatine supplementation in patients with type II diabetes - Oskroba, Aleksander; Pawlina, Mateusz; Orzechowska, Aleksandra; Ziętara, Karolina; Pawełczak, Natalia; Raksa, Karolina; Zielonka, Bartłomiej; Kowalczyk, Ilona; Pawłowski, Piotr; Stawikowski, Cezary (Journal of Education, Health and Sport, 2023)
Background: Type 2 diabetes mellitus (T2DM) prevalence is disturbingly increasing all over the world. Clinicians and patients need new ways of improving T2DM therapy. Aim of this study: The aim of this study is to present the current scientific literature on the potential hypoglycemic effects of creatine in patients with type 2 diabetes. Material and methods: A systematic review of the scientific and medical literature from the PubMed and Google Scholar databases was carried out. This was achieved according to the keywords: type 2 diabetes and creatine supplementation. 25 items of literature were qualified for analysis. Results and conclusions: Creatine supplementation, when combined with physical activity, improves glycemic control in type 2 diabetic patients. Increased glucose transfer into muscle cells by type 4 glucose transporter (GLUT-4) translocation to the sarcolemma is one of the potential mechanisms explaining these hypoglycemic effects. Creatine has a big potential to become a nutritional therapy adjuvant for type 2 diabetes. However, in order to draw firm conclusions about the efficacy and safety of creatine as a diabetic intervention, larger, longer-term, controlled trials involving type 2 diabetes with variable disease severity and different pharmacological treatments are required.